2015
DOI: 10.1074/mcp.m114.041384
|View full text |Cite
|
Sign up to set email alerts
|

Acetylproteomic Analysis Reveals Functional Implications of Lysine Acetylation in Human Spermatozoa (sperm)

Abstract: Male infertility is a medical condition that has been on the rise globally. Lysine acetylation of human sperm, an essential posttranslational modification involved in the etiology of sperm abnormality, is not fully understood. Therefore, we first generated a qualified pan-anti-acetyllysine monoclonal antibody to characterize the global lysine acetylation of uncapacitated normal human sperm with a proteomics approach. With high enrichment ratios that were up to 31%, 973 lysine-acetylated sites that matched to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 57 publications
5
31
0
Order By: Relevance
“…Moreover, as portrayed from the study, diabetic animal had depleted spermatogenic epithelial cells and cytoplasmic vacuolations with detachment of spermatogenic cells from the basement membrane. These abnormalities were related to the necrospermia and astenospermia [44,45]. This finding is line with recent study which reported that the necrosis of spermatogenic epithelium cells was connected to the low sperm count, reduced sperm motility and depleted daily sperm production [46].…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, as portrayed from the study, diabetic animal had depleted spermatogenic epithelial cells and cytoplasmic vacuolations with detachment of spermatogenic cells from the basement membrane. These abnormalities were related to the necrospermia and astenospermia [44,45]. This finding is line with recent study which reported that the necrosis of spermatogenic epithelium cells was connected to the low sperm count, reduced sperm motility and depleted daily sperm production [46].…”
Section: Discussionsupporting
confidence: 81%
“…Lysine acetylation is essential for sperm motility and fertilization as shown by the interference in such processes by histone acetylase inhibitors and anti-acetyllysine antibodies [106]. Lysine acetylproteome was compared between uncapacitated and capacitated sperm [107,108]; different acetylation profiles were observed for functional proteins involved in sperm capacitation, sperm-egg recognition, sperm-egg plasma fusion, and fertilization. Phosphorylation, as resulting from the balance between the catalytic action of kinases [109] and phosphatases [110], is also of key importance in the mechanisms of sperm maturation and capacitation.…”
mentioning
confidence: 99%
“…According to the report by Butler et al, acetylation of epithelial Na + channel elevated the channel abundance and plasma membrane expression by antagonizing ubiquitination and protein degradation [94]. Blockage of acetylation on K74 in voltage-dependent-anion channel was reported to decrease sperm motility [95]. Based on this scarce literature, acetylation is involved in the regulation of conductance, selectivity, trafficking, and turnover of ion channels and subsequently exerts different physiological functions.…”
Section: Acetylation Of Trpc6mentioning
confidence: 99%